Cardiac catheterisation laboratory procedures and in-hospital outcomes at a tertiary facility: A 1-year review from Groote Schuur Hospital, Cape Town, South Africa - Beyers, B; Hitzeroth, J (SA Heart Journal, 2026)
Background: Cardiovascular disease (CVD) is the leading cause of death in South Africa; however, comprehensive data on public-sector cardiac catheterisation laboratory (cath lab) procedural patterns and outcomes remain scarce. Methods: We conducted a retrospective observational study using the Groote Schuur Hospital Cardiac Catheterisation (GSH-CATH) registry at Groote Schuur Hospital (GSH), Cape Town, South Africa, analysing all adult patients undergoing non-electrophysiology procedures between December 2022 and November 2023. Results: A total of 1 694 procedures were performed in 1 239 patients (median age of 58 years, 60.5% female). The primary indications were acute coronary syndrome (ACS) (56.7%) and valvular heart disease (17.7%), with diagnostic coronary angiography (DCA) (40.9%), DCA with percutaneous coronary intervention (PCI), or PCI only (26.0%) being the most frequent procedures. Cardiovascular risk factors were highly prevalent, including hypertension (65.4%), smoking (44.1%), and diabetes (32.5%). The overall procedural complication rate was 6.5%, primarily driven by access-site events (3.2%). Intra-procedural and in-hospital mortality rates were 0.3% and 3.6%, respectively. Systemic hypertension was significantly associated with procedural complications (p = 0.03). Conclusion: This study provides the first comprehensive evaluation of cath lab activity at a South African tertiary facility, highlighting high procedural volume and a unique female-dominant demographic, despite a high proportion of patients requiring emergency or time-sensitive interventions. These findings establish a baseline for quality improvement and resource allocation in the South African public health sector.